2005
DOI: 10.1093/mutage/gei003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential genotoxicity of the phosphate binder lanthanum carbonate

Abstract: Lanthanum was evaluated for potential genotoxicity using a range of in vitro assays (as the carbonate) in the presence and absence of post-mitochondrial fraction (S9) and in vivo in three independent tests for mutagenicity and clastogenicity (as the carbonate and chloride). The drug was devoid of mutagenic activity in bacterial assays (maximum concentration 5000 microg/plate) using a range of test strains (Salmonella typhimurium TA1535, TA1537, TA1538, TA98, TA100 and TA102 and Escherichia coli WP2 uvrA and WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In toxicology studies, it was well tolerated in both normal and uremic (5/6th nephrectomized) animals at doses up to 20 times those recommended for clinical treatment, with no aluminum-like toxicities or other effects of concern for clinical use. [11][12][13] The safety evaluation program included lifetime administration studies in mice and rats. After intravenous dosing, the primary target organ for toxicity was the liver, with significant effects occurring at plasma lanthanum concentrations 20 000 times higher than steady-state levels in dialysis patients.…”
Section: Lanthanum Carbonate [La 2 (Co 3 )mentioning
confidence: 99%
“…In toxicology studies, it was well tolerated in both normal and uremic (5/6th nephrectomized) animals at doses up to 20 times those recommended for clinical treatment, with no aluminum-like toxicities or other effects of concern for clinical use. [11][12][13] The safety evaluation program included lifetime administration studies in mice and rats. After intravenous dosing, the primary target organ for toxicity was the liver, with significant effects occurring at plasma lanthanum concentrations 20 000 times higher than steady-state levels in dialysis patients.…”
Section: Lanthanum Carbonate [La 2 (Co 3 )mentioning
confidence: 99%
“…DOI 10.1002/em 2010). No genotoxicity data exist on this compound although another phosphate binder, called lanthanum, has shown to be nongenotoxic both in vitro and in vivo assays (Damment et al, 2005). Our results show that patients who took this drug do not have any increase in the levels of DNA damage observed either by the comet or by the micronucleus assays.…”
Section: Discussionmentioning
confidence: 62%
“…Brewster et al (2005) found that, although increased microbial colonization of catheters after iron administration exists, intravenous iron administration was not associated with acute microbial growth or clinical infection. No genotoxicity data exist on this compound although another phosphate binder, called lanthanum, has shown to be nongenotoxic both in vitro and in vivo assays (Damment et al, 2005). Sevelamer is a calcium-free, metal-free phosphate binder that offers control of hyperphosphatemia without increasing calcium levels, which would accelerate blood vessel calcification, decreasing serum levels of phosphorus and parathyroid hormone (PTH) in HD patients (Chertow et al, 2002;Pieper et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lanthanum is administered as a phosphate binder in chronic renal failure as lanthanum carbonate. In the course of the clinical trials many studies were performed which showed no toxicity, although lanthanum accumulated in different organs 22, 23. With respect to bone Bervoets et al showed an osteomalacia in lanthanum carbonate treated rats in combination with an accumulation of lanthanum in the bone 24.…”
Section: Discussionmentioning
confidence: 99%